Non-formal Learning And The Acquisition Of Skills – How Does The EU Support Youth Employment? - Wochowska, Małgorzata (Comparative Economic Research. Central and Eastern Europe, 2015)
In recent years the issue of youth unemployment has been identified as one of the most pressing for young people, who are affected particularly hard by the economic crisis in the European Union. In response, the EU institutions have designed and introduced a complex mix of political instruments, agencies, programmes and studies that are supposed to establish a complementary and systemic approach to education and youth policies. Youth policy, as a socioeconomic field of EU political intervention began in 2014 to be subject to a paradigm of employability and “the economy of fighting the crisis”, including issues such as non-formal and informal learning and youth work outside of schooling systems. Thus the EU policy in question has significantly shifted from “personal and cultural development, and inspiring a sense of active citizenship among young people,” as it was formulated in the Youth in Action Programme 2006-2013, towards “the acquisition of professional skills of youth workers, validation systems of non-formal learning, and greater complementarities with formal education and training”, as it is formulated in the Youth Sector of the EU programme for Education - Erasmus+ 2014-2020. The objective of this article is to provide a comparative insight into the context that frames the design of EU policies aimed at mitigating the phenomenon of unemployment among young people, and to show how this has changed in light of the new EU programming period.